Roderick Chisholm on Reliabilism: Implications for Epistemic Indubitability - Ihejirika, Dr. Cardinal; Victor Chizi IHUNDA (RADINKA JAYA UTAMA PUBLISHER, 2023)
This paper aims at examining the pitfalls of Roderick Chisholm’s concept of reliabilism and its implications for epistemic indubility. Chisholm posits that justified belief depends on what is practically true and right for the knower to believe. He maintains that epistemic justification depends on evidence internally available to the knower and anchored his argument on the fact that we rarely have direct access to the truth of propositions, that is, to reality. Every conclusion about the epistemic status of a belief in this perspective involves a conclusion about the “legitimacy” of its source. Our paper argues that this premium Chisholm’s reliabilism places on the knowing subject’s ability to acquire knowledge through the right kind of source undermines our quest for epistemic indubitability hence, among the purposes of this study are: to examine how the reliability of a belief is dependent on the authenticity of its process of realization. It investigates what constitutes the criteria for a reliable belief and tries to resolve whether reliability is conferred on beliefs by our mere confessions. We find that a reliable belief may not after all be error free. Also that reliability invokes the skeptical question of the reliability of human knowledge. Our research which adopts the analytical method of enquiry concludes by underscoring the fact that Chisholm’s reliabilism turns the indubitable knowledge quest of philosophy into doubtful probabilities and further into full blown skepticism.